(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present study aimed to investigate whether two experiential avoidance measures, the AAQ-II and na IRAP, would predict the participant’s performance during an avoidance task. The procedure consisted of three phases: (1) answering questionnaires (including the AAQ-II); (2) responding an IRAP developed to assess EE; (3) responding to an avoidance test. Data collection was individualized. Adult participants composed two groups depending on their performance on the final task: Avoidance=0 (participants who did not emit any avoidance response during the test; n = 17) and Avoidance>2 (participants who emitted at least three avoidance responses; n = 18). There was no difference between groups regarding the AAQ-II scores. On the other hand, participants from the group Avoidance>2 responded faster to “true” on those IRAP trials that presented phases related to avoiding negative private events – compared to the group Avoidance=0. The effect of relational responding on the occurrence of EA is discussed.